2022
DOI: 10.3390/v14020393
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Innate Antiviral Profiles in the Intestinal Lamina Propria Cells of Chickens Infected with Infectious Bursal Disease Viruses of Different Virulence

Abstract: Infectious bursal disease virus (IBDV) is one of the most important infectious diseases of poultry around the world. Gut-associated lymphoid tissues (GALT) are the first line of defense of the host against the infection. The purpose of this study was to investigate the role of innate immune antiviral signaling triggered by Toll-like receptor 3 (TLR3), as well as macrophage activation and cytokine response in the intestinal lamina propria (ILP) cells after the oral challenge of IBDV in relation to IBDV virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…In Nakanishi et al 's review (71), IL-18 normally can enhance the IL-12-driven Th1 immune responses after stimulation, however, it can also stimulate Th2 immune responses in the absence of IL-12; further, overproduction of IL-18 is responsible for tissue injury. Considering the histological changes observed in the thymus, it is conceivable that a predominant Th2 cell response may be underway during this stage of infection, potentially exacerbating disease progression, which consistent with our previous research, where we reported that Th2 cell response plays important role in the IBD progression (72). In this study, we also detected cytokines, chemokines at the mRNA level as evidenced by up-regulation genes enriched in the cytokine-cytokine receptor interaction pathway which is consistent with many researches (15,16).…”
Section: Discussionsupporting
confidence: 92%
“…In Nakanishi et al 's review (71), IL-18 normally can enhance the IL-12-driven Th1 immune responses after stimulation, however, it can also stimulate Th2 immune responses in the absence of IL-12; further, overproduction of IL-18 is responsible for tissue injury. Considering the histological changes observed in the thymus, it is conceivable that a predominant Th2 cell response may be underway during this stage of infection, potentially exacerbating disease progression, which consistent with our previous research, where we reported that Th2 cell response plays important role in the IBD progression (72). In this study, we also detected cytokines, chemokines at the mRNA level as evidenced by up-regulation genes enriched in the cytokine-cytokine receptor interaction pathway which is consistent with many researches (15,16).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the chTLRs above‐mentioned, chTLR3, chTLR5 and chTLR15 were upregulated after chickens were infected with E. tenella . chTLR3 stimulates immune system responses by recognising double‐stranded RNA of viruses, and expression level of chTLR3 was higher in the early stages of infection, and correlated with virulence and viral load during IBDV infection 46 . In the present study, chTLR3 expression was highest at 72 h post‐infection with E. tenella , consistent with IBDV infection.…”
Section: Discussionsupporting
confidence: 75%
“…chTLR3 stimulates immune system responses by recognising double-stranded RNA of viruses, and expression level of chTLR3 was higher in the early stages of infection, and correlated with virulence and viral load during IBDV infection. 46 In the present study, chTLR3…”
Section: Changes In Hdp Gene Expression In the Caecum Of E Tenella-in...mentioning
confidence: 45%
“…Infectious bursal disease (IBD) is an acute, highly contagious viral infection of young chickens that has lymphoid tissue, especially the bursa of Fabricius as its primary target (Berg, 2000). IBDV infection has the ability to lyse B lymphocytes and destroy the follicular centres of bursa, leading to severe immunosuppression due to a failure to replenish B cells in a timely manner (Chen et al., 2022; Wang, Huang, Zhang, et al., 2021). Two serotypes of IBDVs have been recognized: serotype 1 (pathogenic) and serotype 2 (nonpathogenic) (Ismail et al., 1988; Jackwood et al., 1982).…”
Section: Introductionmentioning
confidence: 99%